An Optimal Control Framework for Resources Management in Agriculture. (23rd September 2013) - Lobo Pereira, Fernando; Fontes, Fernando Arménio; Ferreira, Maria Margarida; Pinho, Maria do Rosário; Oliveira, Vilma Alves; Costa, Eduardo; Silva, Geraldo Nunes
Abstract : An optimal control framework to support the management and control of resources in a wide range of problems arising in agriculture is discussed. Lessons extracted from past research on the weed control problem and a survey of a vast body of pertinent literature led to the specification of key requirements to be met by a suitable optimization framework. The proposed layered control structure—including planning, coordination, and execution layers—relies on a set of nested optimization processes of which an "infinite horizon" Model Predictive Control scheme plays a key role in planning and coordination. Some challenges and recent results on the Pontryagin Maximum Principle for infinite horizon optimal control are also discussed.